Tudomány és gazdaság : Festetics Imre gróf birtokai és gazdálkodása a 19. század első harmadában - Kaposi, Zoltán (Közép-Európai Közlemények, 2016)
This study is about a member of the Count Festetics family, who has longly been neglected in researches. The younger brother of the „great” Count György Festetics, Imre Festetics was forgotten by History. He only came to the front a few decades ago when it was unveiled that his experiments on sheep stood out of his time. Since he published his results in 1819 it is reasonable to believe that he was one of the first who dealt with Genetics. Our study examines what sort of familiar and financial background the count had and what his research opportunities had provided. The question is also interesting because it is known that his elder brother, György held together the familiar estates, so Count Imre had to earn his living in an other way. In our study we present that in case of Count Imre both his land acquired through his marriage and the rationalisation of his management provided the solution. After the count gained power over his lands he played an impportant role in its modernisation (land drainings, effective sheep hubandry, crop rotation, etc...).